Рослинність Каховської арени та її зміни за 75 років - ДУБИНА, ДМИТРО ВАСИЛЬОВИЧ; ДЗЮБА, ТЕТЯНА ПАВЛІВНА; ТИМОШЕНКО, ПАВЛО АНДРІЙОВИЧ (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
Рослинність Каховської арени та її зміни за 75 років